Validity and Reliability of Knowledge, Attitude and Practice (KAP) Scale for Dog Bite Prevention in Children - Syahrizal, Abdul Halim; Rosalia, Saimon; Parveen Kaur, Sarjeet Singh; Razitasham, Safii (Universiti Malaysia Sabah, 2020)
Introduction: Rabies is a highly fatal disease that is mostly caused by a dog bite. The Dog Bite Prevention KAP scale is a 30-item scale that is designed to measure children’s level of safety knowledge on dog’s behaviour, precautionary behaviour around dogs, perceived vulnerability towards dogs and help-seeking behaviour following a dog bite. Therefore, this study aimed to determine the test-retest reliability and validity of outcome measures.Methods: This questionnaire was administered to samples of school student aged from 13 years to 14 years at a secondary school located in Bau District, Sarawak. They were purposively selected for a baseline interview (Time 1) anda ten-day follow-up (Time 2). This study was conducted within four months, which were from 10 April to 31 August 2018. Descriptive analysis, content analysis, Cronbach’s alpha, intra-class correlation and exploratory factor analysis were performed in thisstudy.Results: A total of 64 boys and 114 girls were involved in the study, whereby 79.2%, 10.1%, 7.9%, 2.2% and 0.6% of them were of Bidayuh ethnic, Chinese, Iban, Malays and other ethnic, respectively. The Cronbach's alpha was 0.796. The test-retest intra-class correlation was adequate, with 0.84 for perceived vulnerability towards dogs and 0.81 for precautionary behaviour around dogs. Principal components analysis with varimax rotation resulted in two factors, which explained 39% of the variance (perceived vulnerability towards dogs) and 49% of the variance (precautionary behaviour around dogs).Conclusion: The questionnaire is a valid and reliable tool for a dog-bite prevention survey.